WAYS OF STRENGTHENING FOOD SECURITY BY INCREASING THE COMPETITIVENESS OF THE DOMESTIC AGRICULTURAL MARKET (Marketing Journal, 2025)
This article addresses the development of scientifically and practically significant proposals and recommendations aimed at the comprehensive development of the agricultural products market in the agrarian sector within the framework of free market princip les. The study focuses on improving market competitiveness, ensuring food security, and maintaining sustainable development of the agrarian market under current economic and environmental conditions.
Keywords: global climate change; competitiveness of the domestic agrarian market; food security; contractual relations; healthy economic competition; ecological balance; legal framework; average price; system of criteria and indicators